ANALYSIS OF THE ADIWIYATA SCHOOL PROGRAM ON THE DEVELOPMENT OF CLEAN LIFE CHARACTER STUDENTS IN SDN GIWANGAN YOGYAKARTA - Kurniasari, Candra; Susanto, Moh. Rusnoto; Khosiyono, Banun Havifah Cahyo; Cahyani, Berliana Henu; Arumsari, Mela Dina; Selimanorita, Shafa` (International Journal of Engagement and Empowerment (IJE2), 2024)
The purpose of this study is to help learners gain an awareness and sensitivity to the environment and its various problems, help learners to gain a fundamental understanding of how the environment functions, how people interact with the environment and help learners gain experience and skills and use their knowledge in making decisions, positive actions and problem solving related to environmental issues. The method used is qualitative description. This research was conducted at SD Negeri Giwangan involving all students from grade one to grade six. Testing the validity of data using data triangulation techniques, namely combining various existing data and sources in various ways and within a certain time span. Data collection techniques used observation, interview and documentation techniques. Data analysis techniques are data collection, data reduction, data presentation, and conclusion drawing. The results of this study are the role of teachers in instilling the character of clean living can be seen from the habit of washing hands, carrying out picket according to schedule, throwing garbage in its place.  And the supporting factors are the active role of the family, especially parents, student awareness, the active role of the class teacher and infrastructure. While the inhibiting factors are family factors, environmental factors and students. The solution in overcoming this is to provide guidance, teachers advise students to obey the existing rules, make an agreement on the existence of a violation, and provide sanctions for those who break the rules and integrate clean living character values into learning, and collaborate between schools and parents in overcoming these problems because SD Negeri Giwangan is a school with the title of Adiwiyata Mandiri School so that student awareness in protecting the environment and habituation of clean living character is expected to be realized